Trends and Determinants of Contraceptive Use among Young Married Women (Age 15-24) Based on the 2000, 2005, and 2011 Ethiopian Demographic and Health Surveys: A Multivariate Decomposition Analysis - Worku, Abebaw Gebeyehu; Tessema, Gizachew; Zeleke, Atinkut Alamirew (DHS Program, 2014)
Accessing family planning can reduce a significant proportion of maternal, infant, and childhood deaths. In Ethiopia, use of modern contraceptive met hods is low but is increasing. This study aimed to analyze the levels, trends, and determinants of modern contraceptive use and changes over time among young married women in Ethiopia. The study used data from the three Demographic Health Surveys (DHS) conducted in Ethiopia, in 2000, 2005, and 2011. Non-pregnant, young married women age 15-24 were included in the final samples, for sample sizes of 2,157 in 2000, 1,904 in 2005, and 2,146 in 2011. The major statistical techniques used were logistic regression for analysis of determinants of current contraceptive use and logit-based decomposition analysis of factors contributing to the recent changes. STATA 12 was employed for data management and analyses. All calculations presented in this paper were weighted for the sampling probabilities and non-response. Complex sampling procedures were also considered during testing of statistical significance. Among young married women, modern contraceptive prevalence increased from 6% in 2000 to 16% in 2005 and to 36% in 2011. The study found that young women’s wealth status, age, religion, education, family size concordance with husbands, and fertility preference for spacing or limiting births were significantly associated with their use of modern contraception. The decomposition analysis indicated that about a third of the overall change in modern contraceptive use was due to difference in women’s characteristics. For this component, changes in women’s age, educational status, religion, family size concordance, and fertility preference were significantly associated with change in modern contraceptive use. Particularly, an increase in women’s attainment of primary and above education accounted for about a tenth of the change in modern contraceptive use over the study period. About two-thirds of the increase in contraceptive use was due to difference in coefficients. Change in contraceptive use behavior among the rural population and among Orthodox Christians and Protestants showed a significant contribution to the increase. Other things being constant, about a third of the increase in modern contraceptive use in the past decade was due to change in contraceptive use behavior among the rural population. Programmatic interventions targeting poor, younger (adolescent), illiterate, and Muslim women would help to maintain the increasing trend in contraceptive use among young women in Ethiopia.